PENGARUH DISIPLIN KERJA, KOMITMEN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI BKPP KOTA SEMARANG - Indah Pratiwi Nugraha; Artha Febriana (Lembaga Pengembangan Kinerja Dosen, 2021)
The aim of this research is to analyze and prove the effect of work discipline, work commitment, and work motivation on employee performance at BKPP Semarang City. The population of this research is all government employees (PNS) at BKPP Semarang City which amount is 78 people. Sampling method of this research is census technique. Data analyze of this research is multiple regression analysis. Conclusion of this research is work discipline has a positive effect in performance, work commitment has a positive effect in performance, and work motivation has a positive effect in performance. So, all hypotheses in this research are accepted.